Initiating conservation of a newly discovered population of the Endangered hog deer Axis porcinus in Myanmar. Issue 1 (21st October 2016) - Lwin, Ngwe; Linkie, Matthew; Harihar, Abishek; Aung, Saw Soe; Lin, Aung Ko; Momberg, Frank
Abstract: The unprecedented political and economic reforms taking place in Myanmar offer new opportunities for biodiversity conservation. They also bring new challenges in the form of rapidly growing extractive industry and agriculture sectors that have been weakly regulated and are often unsustainable. The Endangered hog deer Axis porcinus epitomizes many of these conservation challenges, and those facing most deer species in the Indo–Burma hotspot. The hog deer has disappeared from large parts of its range as a result of overhunting and intense conversion of its floodplain grassland habitat for agriculture. We report on a population of hog deer that was discovered in the Indawgyi landscape in central Myanmar in 2012. We conducted the first rigorous assessment of a hog deer population in Myanmar using an occupancy sampling protocol, tested the protocol's robustness using a power analysis, and present the results to guide management intervention. The results from our study site revealed widespread occurrence of the species, with high precision. The population map was then used to inform the development of a conservation management zone within a UNESCO Man and Biosphere Reserve around Indawgyi Lake. The importance of this population for the status of the hog deer in Myanmar remains unknown because documentation of the species has been sparse. Our survey protocol could make a significant contribution to addressing this knowledge gap and setting an informed agenda for conservation of the hog deer both nationally and more widely across the Indo-Burma hotspot.